2011
DOI: 10.1007/s00468-011-0597-z
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of urban pines in Helsinki explored using tree rings and climate records

Abstract: The mortality of Scots pine trees in and around Helsinki has been reported in recent years, but the causalities of these deaths have not so far been rigorously examined. Tree-ring analyses have previously shown to effectively reveal historical growth variability and thus hint at the stress factors behind tree mortality. Here, we analyzed the tree rings of pines in two tree classes (living and dead) from an urban park in Helsinki to reveal their growth variations and to examine the obtained chronologies along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 48 publications
(57 reference statements)
2
14
0
Order By: Relevance
“…Actually, the link between the April air temperatures and Scots pine growth is among the most controversial tree-ring correlations discussed in Finland and adjacent areas. This dendroclimatic association (Laitakari 1920;Holopainen et al 2006;Helama et al 2012;Hordo et al 2011) has not been significant in all studies (e.g., Henttonen 1984). Here, we showed that the April climate could influence the tree-ring growth primarily via soil temperatures.…”
Section: Climatic Signals In the Southmentioning
confidence: 42%
“…Actually, the link between the April air temperatures and Scots pine growth is among the most controversial tree-ring correlations discussed in Finland and adjacent areas. This dendroclimatic association (Laitakari 1920;Holopainen et al 2006;Helama et al 2012;Hordo et al 2011) has not been significant in all studies (e.g., Henttonen 1984). Here, we showed that the April climate could influence the tree-ring growth primarily via soil temperatures.…”
Section: Climatic Signals In the Southmentioning
confidence: 42%
“…Only one tree had a too large diameter for catching the pith and one tree was rotten inside. The relative growth rate (RGR) (Briffa and Melvin, 2011;Helama et al, 2012) for each tree was calculated as…”
Section: Dendrochronological Analysismentioning
confidence: 99%
“…Urban trees are influenced by a wide range of various environmental factors and are in danger of being injured and damaged due to the impact of air pollution (Baldasano et al, 2003;Gregg et al, 2003), other forms of anthropogenic load (Pauleit et al, 2002;De Ridder et al, 2004), as well as by unfavourable meteorological factors (Holopainen et al, 2006;Helama et al, 2011). Deciduous trees are more resistant to pollution than conifers; therefore, they are more suitable for planting along the streets and are more common in urban areas than conifers (Helama et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Deciduous trees are more resistant to pollution than conifers; therefore, they are more suitable for planting along the streets and are more common in urban areas than conifers (Helama et al, 2011).…”
Section: Introductionmentioning
confidence: 99%